Analysing Cost Accounting Standards, Practices and Implementations: A Study on Some Selective Manufacturing Companies of Bangladesh - Sohana Sultana; Avijeet Paul; Sumana Podder (Asian Journal of Accounting Perspectives, 2023)
Research aim: This report aims to illustrate a true picture of cost accounting standard practices in different manufacturing organisations in Bangladesh. This article tries to analyse the views of diversified personnel engaged with the cost accounting standards directly or indirectly. Design/Methodology/Approach: The researchers use different statistical tests for this study. It is a quantitative study with a structured questionnaire used to conduct the survey. For analysing the statistical tests, the authors use Microsoft Excel and SPSS 26 along with a three-point Likert scale. Research finding: The results of this study show that most manufacturing organisations operating in Bangladesh practise the Bangladesh Cost Accounting Standards (BCAS). Most of the employees working in manufacturing organisations are familiar with BCAS. This study also finds that BCAS helps in determining costs more accurately and appropriately. This paper further identifies the factors responsible for not implementing BCAS in manufacturing organisations, and lists these firms’ future plans regarding BCAS. The role of Institute of Cost and Management Accountants of Bangladesh (ICMAB) in implementing the standards is also identified here. Theoretical contribution/Originality: This paper will assist researchers and policymakers as well as concerned authorities in getting an overview on the practice and implementation of BCAS in relevant manufacturing organisations. Practitioner/Policy implication: This paper will help manufacturing organisations recognise the significance of practising and implementing BCAS. Research limitation: The small sample size is a substantial limitation of this study. However, future research can be done with a larger data set from different sources.